Embodiment, enaction, and culture: investigating the constitution of the shared world - Durt, Christoph; Fuchs, Thomas; Tewes, Christian (MIT Press, 2017)
The first interdisciplinary investigation of the cultural context of enactive embodiment, offering perspectives that range from the neurophilosophical to the anthropological
Keywords: Aufsatzsammlung; Kultur; Kognition; Geist; Körper